HALAL PRODUCT REVIEW BASED ON TOTAL QUALITY MANAGEMENT AND A SUPPLY CHAIN MANAGEMENT PERSPECTIVE - Yandra Rahadian Perdana (Journal of Industrial Engineering and Halal Industries, 2020)
Halal products are produced through toyyib processes so that they can be used and consumed by consumers, especially Muslims. Toyyib,which isa prerequisite for halal products, is translated asaform of guarantee of the procurement process, material handling, products, and transportation in accordance with Islamic law. The collaboration betweenproducers andsuppliers, distributors, and consumers is the key to implementing supply chain management (SCM) of halal products. Then, the participation of all business actors in the supply chain network to engage in continuous improvement is an articulation of the implementation of total quality management (TQM). The previous literature shows that research that examines halal products from the perspective of TQM and SCM is still limited. Therefore, this paper investigates halal products from the viewpoint of TQM and SCM. Both perspectives are used with the consideration that the toyyib process is not only the responsibility of the producer, but also the responsibility of the supplier, distributor, and consumer. The combination of TQM and SCM is expected to produce a production process for halal products that conformswith Islamic law